Effects of a simulated game on muscle activation in youth baseball pitchers - Oliver, G. D.; Weimar, W. H.; Henning, L. E. (The Journal of Strength and Conditioning Research, 2016)
It is generally accepted that playing with fatigue is a primary predictor of injury in youth baseball because muscular fatigue is believed to alter mechanics during the arm cocking and acceleration phases. Therefore, the purpose of this study was to quantitatively describe gluteal and upper extremity muscle activations in youth baseball pitchers during a simulated game. Twenty-three youth baseball players (11.2 ± 0.8 years; 151.4 ± 8.7 cm; 47.5 ± 10.8 kg) participated. Data were collected through a Delsys Bagnoli-8-channel electromyography system. Single differential electrodes (interelectrode distance: 10 mm) were attached to the bilateral gluteus maximus and medius and throwing side latissimus dorsi, lower trapezius, and serratus anterior and upper trapezius. After warm-up, participants were instructed to throw randomly provided game situations over a regulation distance (46 feet; 14.02 meters) to a catcher. Three, 4-seam fastballs for strikes, thrown in the first and last innings of the simulated game were selected for analysis. A multivariate analysis of variance revealed no statistically significant differences in muscle activity at the 3 phases of the throw, between first and last innings of the simulated game with an observed power of 0.274 (phase 1: foot contact to maximum shoulder external rotation), 0.297 (phase 2: maximum shoulder external rotation to ball release), and 0.226 (phase 3: ball release to maximum shoulder internal rotation). Examining muscle activations as a pitcher approaches fatigue provides information on how long a pitcher can perform before mechanical alterations occur. Although this study did not reveal significant changes, it did reiterate the fact that pitch counts may be working in possibly preventing a youth pitcher throwing to fatigue.